Patient Referral Trajectories in Acute Myocardial Infarction: A Complex Network Perspective - Dâmaso, Lívia C.; Guedes, Bianca R.; Santos, Arthur H. M.; Ito, Márcia; Ulysses, Jesuliana N.; Vieira, Vinícius da F. (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2026: Anais do XXVI Simpósio Brasileiro de Computação Aplicada à SaúdeDO - 10.5753/sbcas.2026.21667, 2026)
This work investigates the application of complex network-based methods to improve the understanding of clinical trajectories for patients with Acute Myocardial Infarction (AMI). By modeling ambulatory care data from São Paulo as a graph, the analysis of patient referral patterns through the perspective of social network science indicates that referral dynamics are not strictly governed by a ‘hierarchy of importance’ or node degree, but highly concentrated spatially, typically organized in a regionalized manner or internally within specific health units. These results suggest that while major hubs coordinate AMI care, referral decisions may be driven more by geographical proximity and immediate availability than by institutional hierarchy. This research provides a baseline for future work in identifying specialist communities and analyzing the impact of socioeconomic factors on cardiovascular care pathways.